Commodity price volatility; output growth and exchange rate dynamics in the Central and Eastern European countries - Żyra, Agnieszka; Shevchuk, Solomiya (Research Papers of Wrocław University of Economics, 2018)
This paper investigates the commodity price effects upon GDP growth and nominal effective exchange rate (NEER) dynamics in several Central and Eastern European (CEE) countries (the Czech Republic, Hungary, Poland and Romania). Our main finding is that an increase in the world commodity price index is a factor behind a uniform exchange rate appreciation across all countries, with an acceleration in output growth in the Czech Republic and Hungary. Except for the Czech Republic, higher commodity price volatility is associated with exchange rate depreciation, while being neutral with respect to output growth. Among some other results, exchange rate dynamics seems to be independent of output growth in three out of four countries, while the effects of a foreign demand shock as proxied by Germany’s industrial production are quite homogeneous across nations
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2018; Nr 509, s. 509-520
Keywords: commodity prices; output; exchange rate; Central and Eastern European (CEE) countries; światowe ceny na surowce; wzrost gospodarczy; kurs walutowy; kraje Europy Środkowej i Wschodniej (ESW)